Analyze and measure the internal factors affecting the profitability of commercial banks: Applied study on the Bank of Baghdad and the Middle East Bank (Entrepreneurship Journal for Finance and Business, 2022)
The aim of the research is to analyze and measure the effect resulting from the internal factors represented by (cash liquidity, debt ratio, capital adequacy, credit facilities to assets, bank size, quality of banking service) affecting the profitability of Iraqi commercial banks represented by the rate of return on assets (ROA) and the rate of return on assets (ROA) and the rate of return on assets. Return on Equity (ROE), and to achieve the goal of the research, a model was built to measure the impact of independent variables on the dependent variable based on the program ( Amos Statistical Analysis Twenty-Fourth Edition ) starting from the application of the multiple linear regression analysis method on a sample of two banks during the period from (2010 -2019), and the research reached a set of results, the most important of which is (there is a significant and statistically significant effect of the internal factors in the profitability indicators (ROA, ROE), and the research showed that the internal factors that most influence the profitability of commercial banks in the study sample differed from one bank to another. It was recommended to strengthen the interest in the capital adequacy ratio, the indebtedness ratio and cash liquidity because of their significant impact on the profitability of commercial banks, the research sample